Rediseño de puestos de áreas administrativas para mejorar estándares de procesos de soporte, Red Salud Sánchez Carrión, 2020 - Tejada Rebaza, Damaris (2021)
The general objective of this research was to determine if the redesign of positions in administrative areas improves the standards of support processes, Sánchez Carrión Health Network, 2020, for which an applied descriptive design was developed, using a pre-experimental type. The study population was the 39 workers of the Sánchez Carrión health network and the survey was used as a technique and the questionnaire as an instrument. As a result, the level of management of the positions of the administrative areas is regular. The standard level of supporting processes before the process redesign was fair. The proposal for the redesign of positions in the administrative area was made. The t test of the difference of the means (averages) obtained before and after the job redesign proposal has a significance level of 0.000 which is less than 0.05; This allows us to accept the hypothesis "The redesign of positions in administrative areas significantly improves the standards of support processes of the Sánchez Carrión 2020 Health Network". The level of the support process standard of the Sánchez Carrión Health Network after the process redesign is good.